Demonstrating Large Scale Industrial CCS through CCU – A Case Study for Methanol Production. (July 2017) - Collodi, Guido; Azzaro, Giuliana; Ferrari, Noemi; Santos, Stanley
Abstract: Methanol is a basic chemical building block used in producing other commodities that we used in our daily lives. In the last decade, due to regulation and policy framework in the transport sector, there is also a significant growth in the use of methanol as fuel (i.e. additives to gasoline, production of MTBE, bio-diesel, synthetic gasoline, etc…). Methanol is produced by reacting CO and CO2 with H2 . Traditionally, this is produced in a two-steps process – i.e. syngas production and methanol synthesis. Most of the CO2 is emitted at the syngas production side of the operation. The question arises if CO2 is captured, what is its potential for the CO2 to be used in the methanol synthesis? What is the limitation of CCU on-site? How could this support the deployment and economics of industrial CCS? This paper aims to present: Techno-economic evaluation of deploying CO2 capture in a mega-methanol plant using NG as feedstock. This plant include a combine reforming process (SMR-ATR configuration) to produce the syngas; methanol synloop and methanol purification unit producing AA grade methanol. Concept of on-site CCU as a possible route to expand future methanol production capacity and at the same time promote the deployment of industrial CCS.